2018
DOI: 10.18325/jkmr.2018.28.2.61
|View full text |Cite
|
Sign up to set email alerts
|

DRF and Single Dose Oral Toxicity Study of ChondroT in Rat

Abstract: Objectives The purpose of this experiment is to evaluate 4 weeks DRF (Dose Rate Finding) and single oral dose toxicity of ChondroT in rats. Methods In 4-week DRF, male and female Sprague-Dawely rats were treated with ChondroT at oral dose of 0, 500, 1000, and 2000 mg/kg. clinical signs, body weight, food consumption, necropsy findings, organ weight, hematological and blood-chemical parameters, and histological findings were monitored for 4 weeks. Also, after single oral administration of ChondroT, mortality, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…For dose selection, we considered the result of previously reported repeated toxicity study (Study No. : TBW-0064-15, 4 weeks repeated toxicity; 0, 500, 1000, 2000 mg/kg) [10] where no significant toxicological changes were found at doses up to 2000 mg/kg. The dose 2000 mg/kg was selected as the high (maximum) dose and two-fold intervals were used for the lower dose levels in the present 13-week repeated dose toxicity study; 1000 and 500 mg/kg were set as the intermediate and low (minimum) doses, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For dose selection, we considered the result of previously reported repeated toxicity study (Study No. : TBW-0064-15, 4 weeks repeated toxicity; 0, 500, 1000, 2000 mg/kg) [10] where no significant toxicological changes were found at doses up to 2000 mg/kg. The dose 2000 mg/kg was selected as the high (maximum) dose and two-fold intervals were used for the lower dose levels in the present 13-week repeated dose toxicity study; 1000 and 500 mg/kg were set as the intermediate and low (minimum) doses, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Studies remain to be conducted on the toxicity of ChondroT . Although a 4-week repeated oral dose toxicity study had shown no adverse effects in Sprague-Dawley (SD) rats administered the maximum recommended dose of 2000 mg/kg/day via oral gavage [10], that study was performed primarily to determine the dosage range for a subsequent 13-week study. Thus, information regarding the oral toxicity of ChondroT during the subchronic period is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…고령화 추세와 더불어 관절염 및 근골격계 질환으로NSAIDs를 장기 복용하는 노인 환자가 증가하고 있으 며 NSAIDs를 장기 복용한 환자의 25%에서 위장관 궤 양이, 이들의 2-4%에서 출혈이나 천공 등의 합병증이 유발되고 있다[33][34][35][36][37] . NSAIDs 복용에 따른 부작용 때문 에 환자별로 치료적 유익성과 부작용 위험성 사이의 균 형을 맞추고자 미국심장학회와 영국 National Institute for Health and Care Excellence (NICE)에서는 가이드라인 을 통해 환자에 맞는 적절한 사용을 권고하고 있다38,39) .증하였으며 동물모델에 대한 단회 및 반복 투여 독성실험을 통해 ChondroT의 무독성량을 설정하였고, 혈소판 응집에 대한 항응고 작용을 확인하였다18,21,25,43,44) .장장애가 유발된SD계의 흰쥐에 골관절염 치료에 사용 되는 천연물 의약품인 Joins Tab 45) 과 선택적 COX-2 억 제제인 Celebrex 46) , 그리고 저용량과 고용량의 ChondroT 를 투여하여 위 산도 측정, 위 내용물 양 측정, cytokine 측정, PGE2 측정, MPO 활성도 측정, erythrocyte와 thrombocyte 측정, 위점막 및 식도점막 손상 측정 및 조 직학적 분석의 과정을 통해 ChondroT가 위장관에 미치 는 영향을 알아보고자 하였다. 실험 기간 모든 군에서 시험물질 투여에 따른 빈사 및 폐사 동물은 관찰되지 않았다.…”
unclassified